2020
DOI: 10.3390/met10070868
|View full text |Cite
|
Sign up to set email alerts
|

The Separation of Aluminum and Stainless-Steel Scraps Using Vibrating Mixed-Size Ball Bed

Abstract: Dry gravity separation using a vibrating zirconia ball bed is proposed in this study to separate aluminum (Al) and stainless steel (STS) scraps obtained from spent hard disk drive recycling. The effects of zirconia ball sizes and vibrating power (vibration amplitude) on the separation efficiency of Al and STS scraps were investigated. The zirconia balls moved down at the center of the vessel and rose with the wall during the vibration test. Although more STS scraps sunk than Al scraps did, the separati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Gravity separation is a consolidated methodology that may be carried out in a dry environment (dry process) or in the presence of water (wet process) [63,92] (Figure 5a). Dry segregation techniques employ air classifiers or ballistic separators in which air is used as the medium to separate lighter materials from heavier ones.…”
Section: Primary and Secondary Recyclingmentioning
confidence: 99%
“…Gravity separation is a consolidated methodology that may be carried out in a dry environment (dry process) or in the presence of water (wet process) [63,92] (Figure 5a). Dry segregation techniques employ air classifiers or ballistic separators in which air is used as the medium to separate lighter materials from heavier ones.…”
Section: Primary and Secondary Recyclingmentioning
confidence: 99%
“…Printed circuit boards (PCBs) are core parts of electric and electronic equipment (EEE) [1][2][3][4][5]. The market of PCBs in Korea grew to 13 trillion Korean won by 2016, and 60% of waste PCBs was recycled, while the rest was exported as used PCBs [6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, dry-type gravity separation can also be modified for recycling applications. Na et al (2020), for example, reported the separation of stainless steel and aluminum from discarded hard disk drives using zirconia balls as separation medium [ 304 ].…”
Section: Critical Discussion Future Perspective and Conclusionmentioning
confidence: 99%